Learning Motivation and Self-Regulation Linked to Academic Procrastination: Motivasi Belajar dan Pengaturan Diri yang Berkaitan dengan Penundaan Akademik - Fatmala, Etik Dwi; Nastiti, Dwi (Indonesian Journal of Education Methods Development, 2025)
General Background: Academic procrastination remains a prevalent issue among high school students, often leading to decreased academic performance and increased psychological distress. Specific Background: Previous studies have identified psychological factors such as learning motivation and self-regulated learning as potential contributors to procrastination. Knowledge Gap: However, limited research has examined the simultaneous influence of these two variables on academic procrastination, particularly among Indonesian high school students. Aims: This study aims to analyze the simultaneous effect of learning motivation and self-regulated learning on academic procrastination among 210 eleventh-grade students at SMA Antartika Sidoarjo. Results: Utilizing a quantitative correlational method and multiple linear regression analysis, the findings indicate a significant effect (F=16.01, p<.001), confirming that both learning motivation and self-regulated learning jointly influence academic procrastination. Notably, 31.43% of students were categorized as having high academic procrastination, while 26.19% and 24.76% showed low levels of learning motivation and self-regulated learning, respectively. Novelty: This study uniquely contributes by investigating the combined impact of these psychological factors on academic procrastination within a senior high school setting. Implications: The results underscore the importance of fostering learning motivation and self-regulation strategies to mitigate academic procrastination in educational interventions and school-based counseling programs. Highlights : Simultaneous influence of motivation and self-regulation is statistically significant. Over 30% of students experience high academic procrastination. Highlights the need for targeted educational interventions. Keywords : Academic Procrastination, Learning Motivation, Self-regulated Learning, High School Students, Psychological Factors